2019
DOI: 10.1088/1475-7516/2019/10/020
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic halo assembly bias and redshift-space distortions

Abstract: We study the effect of large-scale tidal fields on internal halo properties using a set of N-body simulations. We measure significant cross-correlations between large-scale tidal fields and several non-scalar halo properties: shapes, velocity dispersion, and angular momentum. Selection effects that couple to these non-scalar halo properties can produce anisotropic clustering even in real-space. We investigate the size of this effect and show that it can produce a non-zero quadrupole similar in size to the one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…We do not find a degeneracy with 𝑓 𝜎 8 , so the lack of constraint on 𝜎 log 𝑀 and 𝑓 max is not expected to bias our measurement. Numerical simulations have shown that the clustering of dark matter halos can depend on properties other than halo mass, a.k.a halo assembly bias (Sheth & Tormen 2004;Gao et al 2005;Harker et al 2006;Wechsler et al 2006;Obuljen et al 2019). This bias can propagate into the distribution of galaxies that live in these halos and thus introduce additional bias in the clustering measurement.…”
Section: Galaxy-halo Connection Parametersmentioning
confidence: 99%
“…We do not find a degeneracy with 𝑓 𝜎 8 , so the lack of constraint on 𝜎 log 𝑀 and 𝑓 max is not expected to bias our measurement. Numerical simulations have shown that the clustering of dark matter halos can depend on properties other than halo mass, a.k.a halo assembly bias (Sheth & Tormen 2004;Gao et al 2005;Harker et al 2006;Wechsler et al 2006;Obuljen et al 2019). This bias can propagate into the distribution of galaxies that live in these halos and thus introduce additional bias in the clustering measurement.…”
Section: Galaxy-halo Connection Parametersmentioning
confidence: 99%
“…A realistic selection function will smooth the triangle configuration dependence and degrade the constraining power of the bispectrum (Sefusatti & Scoccimarro 2005). Furthermore, galaxy samples selected based on photometric properties can also be impacted by, for instance, the alignment of galaxies to the large-scale tidal fields (Hirata 2009;Krause & Hirata 2011;Martens et al 2018;Obuljen et al 2019). If unaccounted for, this effect can significantly bias the inferred cosmological parameters (Agarwal et al 2020).…”
Section: Forecast Caveatsmentioning
confidence: 99%
“…In [41][42][43][44][45], it is shown that the intrinsic alignments of galaxies induce a selection effect in spectroscopic surveys. Galaxies aligned along the line of sight are more likely to be observed than galaxies aligned perpendicularly to the line of sight.…”
Section: A Mitigating Selection Effects Induced By Intrinsic Alignmementioning
confidence: 99%